If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19g + -4h + 4 + -20(g + -1) = 0 Reorder the terms: 19g + -4h + 4 + -20(-1 + g) = 0 19g + -4h + 4 + (-1 * -20 + g * -20) = 0 19g + -4h + 4 + (20 + -20g) = 0 Reorder the terms: 4 + 20 + 19g + -20g + -4h = 0 Combine like terms: 4 + 20 = 24 24 + 19g + -20g + -4h = 0 Combine like terms: 19g + -20g = -1g 24 + -1g + -4h = 0 Solving 24 + -1g + -4h = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -1g + -24 + -4h = 0 + -24 Reorder the terms: 24 + -24 + -1g + -4h = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1g + -4h = 0 + -24 -1g + -4h = 0 + -24 Combine like terms: 0 + -24 = -24 -1g + -4h = -24 Add '4h' to each side of the equation. -1g + -4h + 4h = -24 + 4h Combine like terms: -4h + 4h = 0 -1g + 0 = -24 + 4h -1g = -24 + 4h Divide each side by '-1'. g = 24 + -4h Simplifying g = 24 + -4h
| x-.7=9.09 | | n+2n+4= | | 7y-27=-32+2y | | 9(k-4)=12 | | 58=-y+179 | | -11x+4+8x-4+3x=0 | | -3x-21=-81 | | -11x+4+8x-4+3x=o | | 5g+7g-4= | | 35x-7y=491 | | 2x+54=2(x+28) | | 4(2x+3)+8=2(X+3)+4 | | -2x-22=-54 | | x+x=270 | | 3(X-5)+25=3X+10 | | 0.5x=0.2+75 | | X+4(2)=3 | | R+r+r+r+r=0 | | cosx^2=1 | | 0.3333x+14=40 | | 4(y-3)+9-3y=0 | | 0=-5X+-2X | | k-7.6=10.35 | | 0.5x^2=4y | | 0.333x+14=40 | | 15x^5+3x^4-40x^3-8x^2-15x-3=0 | | a-25=15 | | C=b-bx-5 | | 18x+2y=34 | | -8+5(g+2)=0 | | 2+0.54t=50 | | -6(4y)-7+2(7y+4)= |